Building Cooling Requirements under Climate Change Scenarios: Impact, Mitigation Strategies, and Future Directions - Ammar M. Khourchid (19420621) (2022)
Climate change affects building cooling demand; however, little has been done to explore this effect and show its variability in different climatic zones. This review organizes and summarizes studies which have simulated the impact of climate change on building cooling requirements, and critically analyzes the effectiveness of the mitigation strategies proposed by these studies to alleviate this impact. The review methodology selected studies that reported cooling demand and discussed mitigation strategies in future climates. The studies were then grouped based on their climate zone and impact period. Analysis showed that climate change will increase building cooling demand in all climatic zones, with the greatest increase occurring in temperate and cold climatic zones. By the middle of the 21st century (2040–2080), the average increase in building cooling demand is expected to reach 33%, 89%, 288% and 376%, in tropical, arid, cold, and temperate climates, respectively. These numbers are expected to increase during the end of the 21st century (2080–2100) to 55%, 302%, 734%, and 1020%, for tropical, arid, cold, and temperate climates, respectively. Some mitigation strategies (e.g., thermal insulation, solar shading) showed a potential to reduce the increase in building cooling demand; however, the reduction varied depending on the strategy and climatic zone. Further research is required to determine if existing cooling systems can handle the future increase in cooling requirements. Other Information Published in: Buildings License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/buildings12101519